Marine mudflat actinomycetes as a novel natural products source - Ryu, Dohee; Hillman, Prima F.; Akinniyi, Ganiyu; Nam, Sang-Jip; Yang, Inho (Frontiers in Marine Science, 2023)
A mudflat is a type of intertidal zone that is alternately affected by terrestrial and marine environments. We searched for examples of research related to the discovery of secondary metabolites in actinomycetes originating from mudflats. In total, we found 16 studies describing 42 natural products. The recognized bioactivities of the secondary metabolites were digested. We also performed a phylogenetic analysis of mudflat-derived actinomycetes. Most of the actinomycete strains belong to the genus Streptomyces. This review underscores mudflat as promising environment for discovering novel actinomycete strains that produce unique bioactive secondary metabolites. This highlights the imperative to explore this distinct environment for marine natural product research.